Occurrence of Spinal Masqueraders in a Urolithiasis Clinical Context - Balagobi, B.; Kandeepan, K.; Thiruvarangan, S. (My University, 2023)
Objective: The purpose of this study is to provide the occurrence of urolithiasis that closely mimicked the somatic nature in the subjective, objective findings and reduction of symptoms with an analgesic. Methods: This study was carried out in a genitourology clinic, Teaching Hospital Jaffna, Sri Lanka for a three months period. The socio-demographics, BMI, and clinical presentation of pain were collected. Results: This study recruited 84 patients, whose mean age was 50.5 ± 15.6 years and the median was 51 years. There were almost two folds male participants (64.3%) and considering the BMI, overweight was the most significant at 52.3% while obesity and underweight were (9.6%) and (5.3%) respectively remain was ideal. The majority (84.5%) had comorbidities including diabetes, hypertension, and dyslipidemia although many had combined them. The subjective clinical presentation was mostly pain and dysuria although the somatic nature of pain complaint was significantly dominated by lower back pain (56%), flank pain (21.4%), loin to groin pain (10.7%), and uretic colic pain (11.9%) despite the uretic colic pain pattern. Conclusion: This can help clinicians to rule out an important aspect of visceral pathologies similar to musculoskeletal clinical presentation to rule in the visceral etiologies that primary symptoms generator.
Keywords: Spinal masqueraders; Premature diagnostic closure; Back pain; Urolithiasis; Differential diagnosis; Clinical decision-making